Preferential tariff formation: The case of the United States - Vivek Joshi (Graduate Institute of International and Development Studies, 2010)
This paper addresses the impact of Multilateral Trade Liberalisation (MTL) on the preferential tariffs granted by the United States. For a given MFN tariff, we model the preferential tariff with a simple linear functional form. We take MTL of the US as known to the world by the end of Uruguay Round in 1994 and estimate its impact on preferential tariff negotiations during 1995 to 2007. We use a three dimensional panel data, which takes into account the partner, product and time variation of the data-set. To complete our data-set, we codify eight PTA legal agreements. We draw three important conclusions. First, the products that are highly protected do not get high preferential access even at the regional level. Second, reciprocity plays only a limited role in granting better preferential access. Third, irrespective of development level of the partner, the non-reciprocal GSP preferences always matter.
Keywords: F13; F15; 330; MFN tariffs; preferential tariffs; reciprocity; GSP; Meistbegünstigung; Handelsliberalisierung; Zollpräferenzen; USA